Le privé est professionnel ? - Isabel Boni-Le Goff (La Nouvelle Revue du Travail)
The article looks at qualified management consultants’ time regimes, highlighting changes in their work patterns and demonstrating how an organisation’s temporal framework can blur the boundaries between professional and private lives. Married consultants with children are at odds with the usual expectation that “unattached” professionals are legitimized because they are more or less permanently available. This is also a highly gendered situation, with female professionals tending to suffer greater employment and career problems. The inherent contradictions are also negotiated differently depending on an individual’s marital status. Egalitarian couples tend to experiment more in an attempt to construct – despite the greater professional and marital instability that they suffer – new parental division of labour and professional practice norms.